Counseling and Blood Pressure Examination Activities in the Coastal Community of Talia, Kendari City as an Effort to Detect Hypertension from an Early Age: Kegiatan Penyuluhan dan Pemeriksaan Tekanan Darah Pada Masyarakat Pesisir Talia Kota Kendari Sebagai Upaya Deteksi Dini Hipertensi - Irma Yunawati; Siti Rabbani Karimuna; L. Lisnawaty; J. Jafriati (Yayasan Ahmar Cendekia Indonesia, 2020)
Hypertension is a disease that is often found in primary health care. Hypertension can increase the risk of cardiovascular disease. One way to prevent hypertension can be done through providing health education, particularly for people who are at risk of developing hypertension. This community service aimed to carry out early detection and increase the knowledge and awareness of the Talia coastal community about hypertension. This community service was carried out in April 2019 with the target of the Talia coastal community. The community service team came from the Faculty of Public Health, Halu Oleo University, which has expertise in the fields of nutrition and public health. This activity consisted of several stages, including the preparation stage which included community surveys, administrative and licensing arrangements, preparation of extension media in the form of leaflets and lecture materials, as well as preparing the tools used for blood pressure examinations, while the implementation stage included counseling in the form of lectures and leaflet distribution on hypertension and blood pressure examinations to the target community. Based on the results of observation, this activity was qualitatively considered successful even though it was still not optimal. Indicators of success can be shown through the ease of licensing and assistance from the Head of Talia Village, the target community who obtained knowledge about early prevention and proper control of hypertension, the community who found out their respective blood pressure, so they can be more aware of the importance of a healthy and balanced life and will regularly to check their blood pressure, and always actively participate until the end of the event. Abstrak Hipertensi merupakan penyakit yang sering ditemukan pada pelayanan kesehatan primer. Hipertensi dapat meningkatkan risiko terjadinya penyakit kardiovaskular. Salah satu cara pencegahan hipertensi yaitu melalui pendidikan kesehatan terutama pada masyarakat berisiko. Tujuan pengabdian masyarakat ini yaitu melakukan deteksi dini serta meningkatkan pengetahuan dan kesadaran masyarakat pesisir Talia tentang hipertensi. Pengabdian masyarakat ini dilakukan pada bulan April 2019 dengan sasaran masyarakat pesisir Talia. Tim pengabdian berasal dari Fakultas Kesehatan Masyarakat Universitas Halu Oleo yang memiliki kepakaran di bidang gizi dan kesehatan masyarakat. Kegiatan ini terdiri dari tahap persiapan meliputi survey masyarakat, pengurusan administrasi dan perizinan, penyusunan media penyuluhan dalam bentuk leaflet dan materi ceramah, serta persiapan alat yang digunakan untuk pemeriksaan tekanan darah, sedangkan tahap pelaksanaan meliputi penyuluhan dalam bentuk ceramah dan pembagian leaflet tentang hipertensi serta pemeriksaan tekanan darah kepada masyarakat sasaran. Berdasarkan pengamatan, secara kualitatif kegiatan ini dapat dikatakan berhasil meski belum maksimal. Indikator keberhasilan dapat ditunjukkan melalui kemudahan perizinan dan bantuan dari Lurah Talia, masyarakat sasaran mendapatkan pengetahuan tentang upaya pencegahan dini dan pengendalian yang tepat terhadap hipertensi, masyarakat sasaran mengetahui tekanan darah masing-masing, sehingga ke depannya dapat lebih menyadari pentingnya hidup sehat bergizi seimbang dan rutin memeriksakan tekanan darah, serta keterlibatan peserta secara aktif sampai akhir acara.